Evolution of HLA-B*5703 HIV-1 escape mutations in HLA-B*5703-positive individuals and their transmission recipients. - Crawford, H; Lumm, W; Leslie, A; Schaefer, M; Boeras, D; Prado, J; Tang, J; Farmer, P; Ndung'u, T; Lakhi, S; Gilmour, J; Goepfert, P; et al. (2009)
HLA-B*57 is the class I allele most consistently associated with control of human immunodeficiency virus (HIV) replication, which may be linked to the specific HIV peptides that this allele presents to cytotoxic T lymphocytes (CTLs), and the resulting efficacy of these cellular immune responses. In two HIV C clade-infected populations in South Africa and Zambia, we sought to elucidate the role of HLA-B*5703 in HIV disease outcome. HLA-B*5703-restricted CTL responses select for escape mutations in three Gag p24 epitopes, in a predictable order. We show that the accumulation of these mutations sequentially reduces viral replicative capacity in vitro. Despite this, in vivo data demonstrate that there is ultimately an increase in viral load concomitant with evasion of all three HLA-B*5703-restricted CTL responses. In HLA-B*5703-mismatched recipients, the previously described early benefit of transmitted HLA-B*5703-associated escape mutations is abrogated by the increase in viral load coincident with reversion. Rapid disease progression is observed in HLA-matched recipients to whom mutated virus is transmitted. These data demonstrate that, although costly escape from CTL responses can progressively attenuate the virus, high viral loads develop in the absence of adequate, continued CTL responses. These data underline the need for a CTL vaccine against multiple conserved epitopes.